The Metropolitan reformatory a regional rehabilitation center for male youth offenders - Pacho, Marie Abigail C. (College of Architecture, University of the Philippines Diliman, 2016)
Crimes continuously threaten the peace and security of a nation and inhibit its holistic progress. The significance of juvenile delinquency as a contributor to criminal activities in the Philippines had been undetermined until the turn of the twenty-first century. Through the passage of the Juvenile Justice and Welfare Act in 2006, children in conflict with the law (CICL) gained nationwide sympathy. Under this limelight, the multifaceted condition of the CICL was recognized and, since then, efforts have been made to safeguard their dignity while undergoing rehabilitation. This goal, however, remains far fruition as thousands of CICL still experience undignified living inside poorly designed correctional facilities. This thesis aims to reduce recidivism among Filipino CICL through the design of a regional rehabilitation center for male youth offenders, aged 17 to 21, who are undergoing a suspended sentence. The Metropolitan Reformatory delves into the personal and legal profiles of the CICL and looks into their behaviors. The design of the reformatory draws its roots from the synthesis of psychological and sociological studies on juvenile delinquency and youth offenders. It focuses on increased interaction among all users and on the minimal utilization of physical barriers to achieve balance between security and CICL autonomy.